Artificial intelligence content in skincare marketing: A systematic literature review - Antonius Felix; Ainur Rofiq; Nanang Suryadi; Arta Moro Sundjaja; Johanes Fernandes Andry (Universitas Nusa Cendana, 2026)
This systematic review aims to synthesize recent research on artificial intelligence (AI) content in skin care product marketing by analyzing technological approaches, consumer perceptions, effectiveness, ethical considerations, and identifying research gaps to guide future research. The research method involved a comprehensive systematic search using the Google Scholar database, covering publications from 2018 to 2025. The results of this study show that the application of AI in skin care product marketing focuses on five main areas: (1) personalized product recommendations and diagnostics, (2) conversational AI and chatbots, (3) virtual trials and augmented reality experiences, (4) AI-generated content and synthetic influencers, and (5) predictive analytics and product configuration. The study concludes that AI content in skincare marketing has the potential to enhance personalization and consumer engagement, but widespread adoption requires addressing challenges related to transparency, privacy, authenticity, and inclusivity. Keywords: Artificial Intelligence; Skincare Marketing; Cosmetics; Personalization; Consumer Behavior